Repurposing of Streptomyces antibiotics as adenosine deaminase inhibitors by pharmacophore modeling, docking, molecular dynamics, and in vitro studies. (2nd January 2020) - Arun, K. G.; Sharanya, C. S.; Abhithaj, J.; Sadasivan, C.
Abstract: Adenosine deaminase (ADA) is an enzyme present in purine metabolic pathway. Its inhibitors are considered to be potent drug lead compounds against inflammatory and malignant diseases. This study aimed to test ADA inhibitory activity of some Streptomyces secondary metabolites by using computational and in vitro methods. The in silico screening of the inhibitory properties has been carried out using pharmacophore modeling, docking, and molecular dynamics studies. The in vitro validation of the selected antibiotics has been carried out by enzyme kinetics and fluorescent spectroscopic studies. The results indicated that novobiocin, an aminocoumarin antibiotic from Streptomyces niveus, has significant inhibition on ADA activity. Hence, the antibiotic can be used as a lead compound for the development of potential ADA inhibitors.